2012
DOI: 10.1111/j.1365-313x.2012.04920.x
|View full text |Cite
|
Sign up to set email alerts
|

Inducible NAD overproduction in Arabidopsis alters metabolic pools and gene expression correlated with increased salicylate content and resistance to Pst‐AvrRpm1

Abstract: SUMMARYPlant development and function are underpinned by redox reactions that depend on co-factors such as nicotinamide adenine dinucleotide (NAD). NAD has recently been shown to be involved in several signalling pathways that are associated with stress tolerance or defence responses. However, the mechanisms by which NAD influences plant gene regulation, metabolism and physiology still remain unclear. Here, we took advantage of Arabidopsis thaliana lines that overexpressed the nadC gene from E. coli, which enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
102
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(109 citation statements)
references
References 72 publications
(155 reference statements)
6
102
1
Order By: Relevance
“…Transient increase in NAD + pools induced resistance to the avirulent bacterial strain Pst-AvrRpm1 via stimulation of the defense hormone salicylic acid (SA). Transcriptomic analyses of nadC plants also pointed to NAD-dependent up-regulation of pathogen-inducible genes associated with Ca 2+ signaling and various redox targets, including the hypersensitive response (HR; Pétriacq et al, 2012Pétriacq et al, , 2013. In support of these results, Mou (2009, 2012) suggested that exogenous NAD + in the apoplast plays a role in defenserelated Ca 2+ signaling via both SA-dependent and SAindependent signaling pathways.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Transient increase in NAD + pools induced resistance to the avirulent bacterial strain Pst-AvrRpm1 via stimulation of the defense hormone salicylic acid (SA). Transcriptomic analyses of nadC plants also pointed to NAD-dependent up-regulation of pathogen-inducible genes associated with Ca 2+ signaling and various redox targets, including the hypersensitive response (HR; Pétriacq et al, 2012Pétriacq et al, , 2013. In support of these results, Mou (2009, 2012) suggested that exogenous NAD + in the apoplast plays a role in defenserelated Ca 2+ signaling via both SA-dependent and SAindependent signaling pathways.…”
mentioning
confidence: 99%
“…Indeed in Arabidopsis (Arabidopsis thaliana), genetic knockdown of aspartate oxidase (AO) activity (EC 1.4.3.16; the first enzyme of de novo NAD synthesis in the chloroplast; Katoh et al, 2006) hampers stomatal immunity against the hemibiotrophic pathogen Pseudomonas syringae pv tomato (Pst; Macho et al, 2012), while AO transcripts consistently build up in response to bacterial infection, presumably to sustain NAD consumption . Furthermore, we have demonstrated previously a direct role for intracellular NAD + in defense, using an inducible system that is based on overexpression of the nadC gene from Escherichia coli, which encodes the NAD biosynthesis enzyme quinolinate phosphoribosyltransferase (EC 2.4.2.19;Pétriacq et al, 2012). Transgenic nadC Arabidopsis plants accumulate NAD upon treatment with quinolinic acid (Q), thereby allowing one to determine the biochemical and physiological consequences of increased NAD content in leaves.…”
mentioning
confidence: 99%
“…This agrees with previous results showing an upregulation of genes associated with Ca 2C response and binding. 4 Hence, direct NAD C treatment is able to induce changes in [Ca 2C ] cyt . To get further insights into the specificity of the [Ca 2C ] cyt response, we then conducted pharmacological treatments using pyridine nucleotides and their derivatives at 1 mM (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…10 While cytosolic Ca 2C peaks are potentiated by elicitors treatments such as the elicitor peptide PEP1, 11,12 AtPEP1 and Ca 2C -responsive genes are upregulated by higher NAD. 4 In addition, trapping of Ca 2C by EGTA prevents the induction of Pathogen Related (PR) genes after treatment with exogenous NAD(P). 13 Hence, NAD and Ca 2C -mediated signal transductions are possibly related.…”
mentioning
confidence: 99%
See 1 more Smart Citation